Reciprocal Associations Between Career Self-Efficacy and Vocational Identity: A Three-Wave Longitudinal Study. (November 2019) - Li, Mengting; Fan, Weiqiao; Cheung, Fanny M.; Wang, Qian
We examined the changes in career decision-making self-efficacy (CDSE) and vocational identity (VI) and their reciprocal associations among 1, 026 senior high school students, comprising 493 from Hong Kong (age in 10th grade: M = 16.31, SD = 0.65; 238 girls) and 533 from Shanghai (age in 10th grade: M = 16.50, SD = 0.56; 237 girls). They completed measures for assessing their CDSE and VI annually from 10th to 12th grades. Latent growth curve analyses indicated that both CDSE and VI significantly increased over time in the Hong Kong sample. Cross-lagged path analyses indicated that the reciprocal positive effects between CDSE and VI over time were supported in both samples. These findings indicated that CDSE and VI are generally dynamic and interrelated dimensions for Chinese adolescents' career development with some regional differences.